Studi Tentang Efektivitas Tanaman Putri Malu (Mimosa Pudica) Sebagai Media Pembelajaran Konsep Sensitivitas Tumbuhan - Emil Yolanda; Nayla; Wisnu Prabowo (CV. KAMPUS AKADEMIK PUBLISING, 2025)
The sensitive plant (mimosa pudica) is one of the unique plants because its leaves can fold when touched or stimulated. This plant has characteristics such as a small stem, sensitive leaves, and thorns around its stem. This plant is the subject of this laboratory work to understand the plant’s sensitivity to environmental stimuli.